Mathematics : a simple tool for geologists - Waltham, David (Blackwell Science, 2000)
This work demonstrates mathematics using geological examples to illustrate mathematical ideas. This approach emphasizes the relevance of mathematics to geology, and gives examples of mathematical concepts in a context familiar to the reader.